Food policy for the poor: Expanding the research frontiers - Highlights from 30 years of IFPRI research - von Braun, Joachim; Pandya-Lorch, Rajul (International Food Policy Research Institute, 2005)
In the mid-1970s it looked like Thomas Malthus’s predictions of runaway population growth and consequent food shortages and famine were coming true. Famines in Bangladesh and Ethiopia had killed hundreds of thousands of people, poor weather had reduced harvests in a number of countries, and world cereal stocks were perilously low. There was talk of food “triage,” in which food-abundant countries would decide who should get food and who should not, thereby dooming some to death. With the new level of alarm over the world’s food supplies, a host of meetings were held and organizations created to search for solutions. One of these organizations was IFPRI.